2005
DOI: 10.1007/s11661-005-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior of bimodal nanostructured 5083 Al alloys

Abstract: Cryomilled 5083 Al alloys blended with volume fractions of 15, 30, and 50 pct unmilled 5083 Al were produced by consolidation of a mixture of cryomilled 5083 Al and unmilled 5083 Al powders. A bimodal grain size was achieved in the as-extruded alloys in which nanostructured regions had a grain size of 200 nm and coarse-grained regions had a grain size of 1 m. Compression loading in the longitudinal direction resulted in elastic-perfectly plastic deformation behavior. An enhanced tensile elongation associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(146 citation statements)
references
References 41 publications
11
135
0
Order By: Relevance
“…According to the model by Lavernia and collaborators [36,37], cracks follow a fast and intergranular path when running through the nanostructured grains, but are blunted and slowed down when they encounter a large and soft grain. The coarse grains in a bimodal grain structure are therefore an important reason to attain large uniform elongation in the 4P sample.…”
Section: Fracture Of Tensile Samplesmentioning
confidence: 99%
“…According to the model by Lavernia and collaborators [36,37], cracks follow a fast and intergranular path when running through the nanostructured grains, but are blunted and slowed down when they encounter a large and soft grain. The coarse grains in a bimodal grain structure are therefore an important reason to attain large uniform elongation in the 4P sample.…”
Section: Fracture Of Tensile Samplesmentioning
confidence: 99%
“…[1] Of the UFG materials that exhibit considerable ductility, an inhomogeneous microstructure (bimodal grain size distribution) is frequently reported. [2,3] For example, in bimodal Al-Mg alloys fabricated via cryomilling, [4,5] a true strain of 6 to 8 pct in tension was obtained. The grain size distribution in this material indicated that the fine grain size is in the range of 100 to 300 nm, whereas the coarse grains centered around 1 lm.…”
mentioning
confidence: 99%
“…A similar approach was previously used for cryomilled materials, including Al, [15] Ni, [39] and Ti [13] alloys. A bimodal or multimodal structure can also be formed via thermomechanical treatments and again provide a high ductility.…”
Section: Mechanical Behaviormentioning
confidence: 99%
“…Also in these studies, quasi-isostatic (QI) forging was used as a consolidation and secondary deformation method. Specifically, a multistep approach was adopted in this study and involved cryomilling, blending with micron-sized powders (to generate a multiscale microstructure), [15] hot vacuum degassing, and QI forging produced materials with a multimodal grain size distribution. In roomtemperature tensile tests, a YS of 840 MPa, a UTS of 902 MPa, and an elongation to failure value of 27.5 pct were measured for these samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation